Gut microbiome signatures in iNPH: Insights from a shotgun metagenomics study - Rahel Park; Claire Chevalier; Silas Kieser; Moira Marizzoni; Arthur Paquis; Stéphane Armand; Max Scheffler; Gilles Allali; Frederic Assal; Shahan Momjian; Giovanni B. Frisoni (PLoS ONE, 2025)
Idiopathic normal pressure hydrocephalus (iNPH), a leading cause of reversible dementia in older adults, is marked by ventriculomegaly, gait disturbances, cognitive decline, and urinary incontinence. Emerging evidence suggests that gut dysbiosis (microbial imbalance) may influence neuroinflammation and cerebrospinal fluid dynamics, potentially contributing to glymphatic system dysfunction and ventricular enlargement. This study used shotgun metagenomics to analyze the gut microbiome in iNPH patients (n = 18) compared to healthy controls (n = 50), individuals with ventriculomegaly but no iNPH symptoms (n = 50), and Alzheimer’s disease patients (n = 50). Microbiome analysis showed an enrichment of species previously linked to various disease states, such as Enterocloster bolteae and Ruminococcus gnavus, indicating general dysbiosis. In contrast, enrichment of specific taxa, including Evtepia gabavorous and Cuneatibacter sp., were specifically associated with iNPH clinical traits, pointing to possible disease-specific microbial markers. Functional analysis showed enrichment of pathways related to carbohydrate and amino acid metabolism, including the S-adenosyl-L-methionine superpathway, implicating inflammatory and immune processes. These findings suggest distinct gut microbiome signatures in iNPH, offering insights into potential gut-brain interactions that may contribute to the disorder’s pathophysiology and highlighting possible targets for future therapeutic strategies.